Evaluation Of Budget Planning And Identification Of Dominant Work In The Building C Construction Project Of Husada Health College, Jombang - Nicko Yoga Pratama Nicko Yoga Pratama; Inge Anggitasari; Olvi Pamadya Utaya Kusuma; Susilowati Susilowati (International Journal of Health Engineering and Technology, 2026)
Budget planning is one of the important stages in the implementation of a construction project because it is related to cost control and the feasibility of project implementation. The availability of adequate educational facilities and infrastructure is an important factor in supporting an effective and quality learning process. Along with the increasing number of students at STIKES Husada Jombang, the need for study space and supporting facilities is also increasing. Therefore, Building C STIKES Husada Jombang, which originally consisted of one floor, is planned to be renovated into two floors to meet the increasing need for space. This study aims to determine the amount of the Budget Plan (RAB) for the construction of Building C STIKES Husada Jombang and to determine the type of work that has the largest cost in the project. The method used in this study is the 2024 Work Unit Price Analysis (AHSP) published by the Ministry of Public Works and Public Housing (PUPR). The data used are in the form of working drawings which are then calculated using unit price analysis to obtain the total cost of the construction work. Based on the results of the analysis of the calculation of the volume of work and the analysis of the unit price of work, the total Budget Plan (RAB) for the construction of Building C of STIKES Husada Jombang was obtained at Rp 1,305,078,971.12. The results of the analysis show that the work on frames, doors, and windows is the work with the largest cost, namely Rp 283,155,850.00, followed by structural work of Rp 281,668,931.12